Matharpacady-21.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The Lion’s Den bungalow is named after the twin lion-mounted gate posts. The lions are associated with the Biblical story of Daniel, who was thrown in the lion's den by Darius the Mede, King of Babylon. Pleased by Daniel’s blameless character, the God of Israel sent an angel to close the jaws of the lions. Thus, Daniel survived the lion's den unharmed and was released by Darius.